Driving MSME performance: exploring the influence of entrepreneurial orientation and business independence - Naidah Naidah; Muhammad Rusydi; Syarifuddin Sulaiman; Buyung Romadhoni; Muryani Arsal (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
The problem of the development of micro, small and medium enterprises (MSMEs) is the most dominant research topic, especially in developing countries that rely on these sectors in their economy. The purpose of this study was to analyze the effect of entrepreneurial orientation on the performance of MSMEs through the mediation of business independence variables. This type of research is field research and literature which aims to answer the formulation of the research problem. The research location is in Makassar City, South Sulawesi. The population in this study is 16.492 MSMEs. The number of samples in this study was determined by the Slovin formula, so the sample size is 100 SMEs. The sampling method is probability sampling with simple random sampling technique, namely proportional random sampling for each business sector. Data analysis techniques use structural equation model analysis. The results showed that the entrepreneurial orientation variable had a significant effect on the performance of MSMEs, both directly and through the business independence variable. Based on the findings of this study, further research is needed regarding the performance of SMEs to explore other variables.